An exploratory investigation of the daily talk time of people with non-fluent aphasia and non-aphasic peers. (4th July 2017) - Brandenburg, Caitlin; Worrall, Linda; Copland, David; Rodriguez, Amy
Abstract: Purpose: This paper presents an exploratory investigation of the talk time of people with non-fluent aphasia, as measured by the CommFit™ app. Aims were to compare the talk time of people with aphasia with non-aphasic peers and measures of impairment, activity and participation. The variability of talk time over weeks and days of the week was also investigated. Method: Twelve people with post-stroke, non-fluent aphasia and seven non-aphasic controls measured their talk time using the CommFit™ app for 6 h/day for 14 days. Result: People with aphasia talked for a mean of 4.5 min/h and non-aphasic controls 7.2 min/h, which was not a significant difference ( p = 0.056). Talk time of people with aphasia was not significantly correlated with WAB-R AQ or CADL-2 scores, but a moderate-high positive relationship between talk time and SIPSO scores was found ( r = 0.648, p = 0.015). Talk time was not significantly different between the first and second weeks of recording for either group, and days of the week were not significantly different except for Saturdays, in which talk time was higher. Conclusion : This study provides some preliminary data on talk time in people with aphasia, suggesting that talk time is an indicator of participation.